Contribution à l’épistémologie de l’évaluation des enseignements par les étudiants - Yvan Abernot; Christine Gangloff-Ziegler; Marc Weisser (Éducation et Socialisation)
The evaluation of the lessons and of the formations by students (E.E.E./E.F.E.) is today one of the indicators of the quality approach undertaken by a university. This kind of device is however variously considered, according to places and cultures. Although it has been recommended since many years and it has been made compulsory since 1997, it is carried out with difficulties in France. To objectify somewhat the positions of the actors concerned, we question three metrological qualities of such a tool, namely the representativeness, the validity, the fidelity. After a review of the literature, we specify these points through a compared experimental study of two devices of E.E.E. set up at the University of High-Alsace and at the University of Aix-Marseilles. We draw some consequences about a formative approach of the E.E.E., within the broader framework of a university pedagogy which is still to build.